CMET-21. A PHASE IB STUDY OF PROTON CRANIOSPINAL IRRADIATION FOR THE TREATMENT OF SOLID TUMOR LEPTOMENINGEAL METASTASES. (11th November 2019) - Jonathan Yang, T; Wolden, Suzanne; Yamada, Josh; Mehallow, Michelle; Skakodub, Anna; Young, Robert; Gavrilovic, Igor; Lin, Andrew; Santomasso, Bianca; Grommes, Christian; Piotrowski, Anna; Schaff, Lauren; et al.
Abstract: Leptomeningeal metastases (LM) is associated with limited survival and treatment options for patients with solid tumor malignancies. While focal radiotherapy is effective for local palliation, it lacks durability due to cerebrospinal fluid (CSF) tumor cells reseeding. Craniospinal irradiation (CSI) in contrast treats the entire central nervous system (CNS) compartment thus potentially improves disease control. We performed a phase IB study of proton CSI using 30CGE in 10 fractions for treating solid tumor LM (NCT03520504). The primary end point is dose-liming toxicity (DLT) within 1 month of treatment. Clinical outcomes and CSF circulating tumor cells (CTCs) by CellSearch ® were evaluated. Overall (OS) and progression-free survival (PFS) were assessed using Kaplan-Meier estimates. Of the 24 patients enrolled, 4 were excluded from analysis: 3 did not complete treatment due to CNS or systemic disease progression (PD), and 1 completed treatment outside study window. The majority of patients had metastatic lung (55%) and breast (30%) malignancies. At this submission, the median follow-up was 2.8 months (0.5–9.4 months). No DLT was observed. Treatment-related grade 2+ toxicities were: fatigue (G2=43%), anorexia (G2=5%), anemia (G2=10%), thrombocytopenia (G3=5%, G2=10%), and leukopenia (G3=14%, G2=14%). Median survival is not reached with 17 patients (85%) alive with stable/improved LM including 2 with durable CNS control for >9 months, 1 patient alive with CNS and systemic PD at 3.7 months, 2 patients died at 3.6 and 5.1 months with CNS and systemic PD. At 3-month, OS and PFS were 100% and 90% (95% CI 100–72%), respectively. In the 13 patients with CSF CTCs evaluation, decreased quantifiable CTCs at 1-month after proton CSI correlated significantly with improved CNS PFS (log-rank p=0.014). These early findings suggest that proton CSI is a safe and potentially effective treatment for patients with solid tumor LM. CSF biomarkers assessment is needed to better elucidate predictors of response.